2018
DOI: 10.1007/s11071-018-4534-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the direct normal form and multiple scales methods through frequency detuning

Abstract: Approximate analytical methods, such as the multiple scales (MS) and direct normal form (DNF) techniques, have been used extensively for investigating nonlinear mechanical structures, due to their ability to offer insight into the system dynamics. A comparison of their accuracy has not previously been undertaken, so is addressed in this paper. This is achieved by computing the backbone curves of two systems: the single-degree-of-freedom Duffing oscillator and a non-symmetric, two-degree-of-freedom oscillator. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The results presented in this paper, along with those of [3], have demonstrated that the MS and DNF are able to provide identical results. Given that the implementation of the two techniques requires a similar number of steps, this leaves the user to make a decision based on the nuances of the particular system they are considering.…”
Section: Considerations For Userssupporting
confidence: 61%
See 4 more Smart Citations
“…The results presented in this paper, along with those of [3], have demonstrated that the MS and DNF are able to provide identical results. Given that the implementation of the two techniques requires a similar number of steps, this leaves the user to make a decision based on the nuances of the particular system they are considering.…”
Section: Considerations For Userssupporting
confidence: 61%
“…These resonances have also been investigated using the DNF method [26][27][28][29], which has been further applied to explore the significance of nonlinear normal modes in relation to forced cases [30] and identify nonlinearity in structures [31,32]. This paper expands the recent discussion by the authors in [3], which considered the calculation of the free response of two nonlinear mass-spring systems using the MS and DNF techniques. The authors applied the frequency detuning from the DNF method, as explored in [33,34], in the MS technique to show that it is possible for both methods to give identical solutions.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations